Apple: from subculture to cultural dominance - Peñaloza, Lisa (Henry Stewart Talks, 2018)
This case study considers the 20th century Apple consuming community to emphasise how new challengers in an industry can be successful by developing and appealing to subcultures. Apple’s ‘Think different’ advertising campaign uniquely positioned the brand as providing distinct, crafted products for the innovative and artistic. However, Apple’s expansion in the 21st century has undermined the exclusivity of its products and with it its appeal to the subculture market.